The nexus of settlement development and today’s energy use in Sary-Mogol, Alai Valley, Kyrgyzstan - Sonntag, Christian (ERDKUNDE, 2016)
Based on a case study of Sary-Mogol, a rural settlement in the Alai Valley in Southern Kyrgyzstan, this paper investigates the relationship between settlement development, resulting in a three-period building structure, and today’s domestic use of energy. The three-period building structure is considered to be a consequence of Soviet resettlement processes and post-Soviet developments such as migration and economic inequality. Until the 1940s, there were no permanent settlements in Sary-Mogol or in the surrounding areas. The settlement Sary-Mogol (3,000 m a.s.l.) was founded in 1946 as an enclave within the borders of the Kyrgyz Soviet Socialist Republic. Administratively, however, Sary Mogol belonged to the Tajik Soviet Socialist Republic, responsible for supplying the collective farms in the Eastern Pamirs (Murghab District, Gorno-Badakhshan Autonomous Region). The resettlement of predominantly Kyrgyz people from the Eastern Pamirs led to the start of the settlement construction. This paper examines the current domestic energy supply situation, which is part of multiple measures and strategies taken by the local population to meet the challenges of sustaining their livelihoods. Furthermore, a historical context since the establishment of the settlement will be given.